La expresión plástica y su relación con el desarrollo de la creatividad de los niños y niñas de primer año de educación básica de la unidad educativa particular “Borja N°3 Cavanis” de la ciudad de Quito, periodo lectivo 2013-2014”. Lineamientos alternativos - Ochoa Chicaiza, Sandra Jeanneth (2014)
This thesis entitled " THE PLASTIC EXPRESSION AND ITS RELATION TO THE DEVELOPMENT OF CREATIVITY OF BASIC EDUCATION FIRST YEAR CHILDREN “CAVANIS BORJA No.3 " SCHOOL QUITO CITY , PERIOD 2013 -2014 " . ALTERNATIVE GUIDELINES. It is structured and developed according to the regulations of graduation from the Loja National University. The general objective that guided the research was : To sensitize teachers about the importance of Artistic Expression for the development of creativity of children in the first grade of elementary school. The methods used for the preparation of this research work were : Scientist, Inductive, Deductive , Analytic , Synthetic , Descriptive and Statistical Model , the techniques used were: Survey addressed to First Year Teachers Basic General Education to establish the types of Plastic expression used in the daily work with children and Observation Guide applied to children to determine the Development of Creativity . The Results of Teacher’s Survey concluded that : 100% of teachers report that Plastic Expression techniques they use most frequently in the daily work are: drawing, painting , sculpture and ceramics, architecture 75% , and 50% photography. Plastic Expression for children is a means of expression and communication that perform naturally and as a game in which they turn their experiences, emotions and experiences. According to results de Observation Guide concludes: 45% of children have a Satisfactory development of Creativity , 41% Very Satisfactory , and Unsatisfactory 14% . Creativity is a complex process of human subjectivity that is expressed in the production of something, which in a sense is new and valuable, so that the difficulties in identification and assessment increase due to the relative nature of these criteria itself